The Definition of Housing with EXPRESS - Bayer, Semih; TÜRKYILMAZ, EMRAH (My University, 2019)
Building Information Modeling (BIM), is a system that uses effectively in all processes in projects. The aim of this system is to increase the quality and speed of interdisciplinary communication and to provide the most suitable product for the end user. Thus, the deployment of BIM in construction can make the industry more effective, flexible and innovative. EXPRESS is the standard data modeling language for product information. With EXPRESS, the data model can define in two ways; written and visual. Written EXPRESS is for notation and EXPRESS-G is for visual representation. EXPRESS defines different data types together with algorithmic rules in a schema. EXPRESS-G uses to visually display entity and species definitions, relationships, and clusters. This study describes a concept of how to use EXPRESS language for the definition of an architectural product. To be able to make this definition, EXPRESS language has examined, and ISO 10303 standards have reviewed. A housing project in the BIM environment has taken as an example and it has defined with EXPRESS. The results demonstrate that it is possible to make the desired calculations related to the housing through EXPRESS. When the definition made through a project which is still in the design phase, it can determine whether the project provides the desired spatial conditions by making any calculations. Thus, high quality and cost-effective projects can achieve. The overall architectural planning processes are no longer carries out linearly but instead in a complex and integrated manner, therefore it seems that classical methods cannot support these processes efficiently. This study is also an effort to strengthen the competitiveness of the building industry by improving planning reliability, quality, and efficiency.
Keywords: EXPRESS; Housing; BIM; ISO 10303